An Assessment of the Passengers’ Satisfaction from Service Quality of Onboard Employees of Saudi Airlines – An Empirical Study - Ansari, Zaid Ahmad (Archives of Business Research, 2016)
Purpose: The main objective of the study was to find out the effectiveness of the Saudia crewmembers in delivering services to the passengers. Methodology: This is quantitative study based on primary data collected from the passengers of Saudi Airlines. A close-ended structured questionnaire had been distributed randomly. The questionnaire was developed in English and translated into Arabic for high response among the passengers who ever travelled by Saudi Airlines. The researcher used Convenience sampling technique to identify the respondents who came from across the country for counseling classes at college of business and writing their final exams. The study sample size was 400 respondents. Findings: The results show that the passengers of the Saudi airlines were only somewhat satisfied not satisfied or highly satisfied. The satisfaction for business class passengers were much less in comparison to economy class passengers, the AlFursan loyalty program members were also comparatively less satisfied than the members, and old passengers satisfaction level was less than the new passengers. Managerial Implications: The onboard employees’ service quality need to be enhanced in general and specially in the business class to improve the passengers’ satisfaction to retain them with Saudi Airlines. Paper Type: Research Paper